Talaromyces marneffei central nervous system infection unveiled by the novel Mp1p antigen detection assay in AIDS patient - Xiaofeng Li; Jing Wang; Jing He; Haiyan Zhang; Ming Luo (BMC Infectious Diseases)
Abstract Background In acquired immunodeficiency syndrome patients, Talaromyces marneffei infections are mostly disseminated and may involve the skin, mucosa, respiratory system, digestive system, lymphatic system, and as some reports indicate, the nervous system. Mp1p, a cell wall-specific polysaccharide in Talaromyces marneffei, is used for laboratory diagnosis of Talaromyces marneffei in blood and urine samples. However, Cerebrospinal fluid Mp1p diagnosis of Talaromyces marneffei central nervous system infection has not been reported. Case presentation We present the case of an acquired immunodeficiency syndrome 35-year-old woman who has had dizziness and headache and was infected with central nervous system Talaromycosis.Magnetic resonance imaging scan which showed intracranial infectious lesions, altered brain atrophic, and periventricular demyelination.The Mp1p antigen was positive by using immunofluorescence in the Cerebrospinal fluid. Talaromyces marneffei was isolated from the Cerebrospinal fluid.After antifungal treatment, her clinical symptoms significantly improved. Conclusions Talaromyces marneffei central nervous system infection is rare. If the patient has symptoms of central nervous system, the Cerebrospinal fluid Mp1p antigen and culture should be performed to make a definitive diagnosis.